Membangun Literasi Akademik Melalui Pelatihan Penulisan Karya Ilmiah untuk Mahasiswa Baru - Musdalifah Musdalifah; Karim, Abdul; Saud, Chaerul Fadlan (Lembaga Pengembangan Kinerja Dosen, 2025)
Academic writing skills are one of the essential aspects of developing students’ academic literacy from the beginning of their university studies. However, most first-year students in the 2025 academic year in the English Department, Faculty of Languages and Literature, Universitas Negeri Makassar, still face difficulties in understanding the structure, language, and ethic of academic writing. This community service aims to improve the academic literacy skills of first-year students through a comprehensive and practical academic writing training program. The implementation methods included several stages, namely pre-test, material presentation, writing exercise, and post-test. The Training materials covered the structure of scientific papers, the use of academic language, paraphrasing techniques, citation ethics, and reference management using reference manager tools. The participants consisted of 40 first-year students who took part in a full-day training session. The results showed a significant improvement in all assessment aspects, with the average score increasing from 56.8 in the pre-test to 83.9 in the post-test. The highest improvement was observed in the accuracy of citation and referencing, which increased by 33.2%. These findings indicate that the training effectively enhanced students’ understanding of systematic and ethical principles of academic writing. Therefore, this activity contributes to strengthening the academic culture and preparing students for academic writing during their studies.